DIFFERENCES IN SALIVARY VOLUME, PH, AND ORAL CONDITIONS OF DIABETES MELLITUS AND NON-DIABETES MELLITUS PATIENTS - Dahlia Salsa Farhani; Sri Tjahajawati; Anggun Rafisa (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: The Prevalence of diabetes mellitus (DM) has been increasing over the past decades. DM is a chronic metabolic disease characterized by persistent hyperglycemia, which impacts various body systems, including the oral cavity. It affects salivary volume, salivary pH, and oral health, leading to conditions such as xerostomia, gingivitis, dental caries, and ulceration. Purpose: This study aimed to determine the differences in salivary volume, salivary pH, and oral conditions in DM patients and non-DM. Methods: This study was an analytic comparative using secondary data from the result of Unpad Lecturer Competency Research (RKDU) by a consecutive sampling of 22 DM women and 22 non-DM women. The numerical data were analyzed using t test or Mann-Whitney test and the categorical data were analyzed using z proportion test with a significance level of p<0,05. Results: The results showed that there were significant differences in salivary volume (p=0,0001), salivary pH (p=2,54E-05), xerostomia (p=0,01), and dental caries (p=0,007), and there were no significant differences in gingivitis (p=0,216) and ulceration (p=0,154) in DM group and non-DM group. Conclusion: There are differences in salivary volume, salivary pH, and the conditions of xerostomia and dental caries, but there are no differences in the conditions of gingivitis and ulceration in DM patients and non-DM. The differences in saliva and oral conditions are caused by autonomy neuropathy, dehydration, alteration in vascularization and immune response, increasing salivary glucose level, and drug consumption.